The 4th Sub-Regional Climate Outlook Forum: IGAD Cluster I, II and III MAM 2025 Season Forecast - IGAD Climate Prediction & Applications Centre (IGAD Climate Prediction & Applications Centre, 2025)
The IGAD Climate Prediction and Applications Centre (ICPAC), in collaboration with the IGAD Centre for Pastoral Areas and Livestock Development (ICPALD), through the "Strengthening Pastoral Livelihoods in the Greater Horn of Africa through Effective Anticipatory Action" (PASSAGE) project, supported by the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), and the Intra-ACP Climate Services and Related Applications (ClimSA) conducted the fourth sub-regional Climate Outlook Forum (Sub-COF 4) from 4-6 February 2025 for the Karamoja cluster in Lodwar, Kenya. The aim of the forum was to review the performance of the previous rainfall season, October-December (OND) 2024, co-develop A downscaled tailored forecast for the March-May (MAM) 2025 season, identify and engage with the major response stakeholders at the national, sub-national, and local levels, and co-develop relevant advisories for important sectors within the Karamoja Cluster. Given the unique climate information needs, vulnerabilities, and societal structures in the region, the community-based indigenous knowledge on climate variability and forecasting was explored towards the development of context-specific advisories for the region. The MAM season is the most important for the Karamoja cluster, with rainfall extending through to August in the western regions (parts of Uganda and South Sudan), but in regions of central to southern Turkana County in Kenya, the rains cease by May. The MAM 2025 forecast indicates a high likelihood of above-normal rainfall over western and northern parts of the Karamoja cluster, including northern Surma, eastern Kapoeta, northern Kapoeta, southern Kapoeta, Budi, Karenga, Kotido, Abim, Napak, Nakapiripirit, West Pokot, as well as southeastern areas such as Turkana South and Turkana East. Conversely, drier-than-normal conditions are expected over central to northeastern Karamoja, including Turkana Central, Loima, Turkana West, Kabong, parts of Moroto, parts of Karenga, Kapoeta East, northern Turkana, Dessanach, Nyangatom, and West Pokot/Kacheliba. Temperatures are largely expected to be warmer than average across the cluster. With participants ranging from various government agencies, humanitarian actors, academia and research, community leaders, youth, women, and NGOs, the forum co-produced advisories relevant to most agro-pastoral livelihoods in the region. These could be summarized in the following key messages from the forum; ●Unequal spatial rainfall distribution may pose risks to crop and pasture production, potentially reducing yields and increasing food insecurity, especially in the eastern regions. ●Investing in improved water infrastructure, such as boreholes and reservoirs, is critical to reduce pastoralists' dependence on rain-fed water sources ●Enhancing collaboration with media and extension officers to improve climate information dissemination. ●Strengthen the linkages between different actors in early warning, research and community systems to ensure there is increased uptake of early warning for early action